Creation intervention programs of social intelligence development for school age children - Melnik, A. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2014)
The concept of components of cognitive, emotional and behavioral components of social intelligence during the school age is considered. Sci- entists' views are described and own approach to the definition of these phenomena is given. Based on the results of the research, the correctional and development program for increasing the level of the development of components of the social intelligence of children of the school age, depending on the characteristics of the development of these components in different age periods is created. Verification of the effectiveness of the proposed program is performed and the necessity of a comprehensive approach, which facilitates the increase of the data of the development levels of some abilities, is proved.
Keywords: social intelligence; correctional and development program; cognitive; emotional and behavioral component; junior; middle and senior school age